PTU-161 Expression of Polo-Like Kinase 1 and Geminin is Up-Regulated in the Squamous-Metaplasia-Dysplasia-Carcinoma Sequence and Correlates with Aneuploidy. (4th June 2013) - Butt, M A; Haidry, R J; Oukrif, D; Dunn, J; Bloom, E S; Louis-Auguste, J; Butter, N; Khan, S-U-R; Sehgal, V; Banks, M R; Rodriguez-Justo, M; Lovat, L B; et al.
Abstract : Introduction: Population based studies have shown a small but significant proportion of patients with Barrett's oesophagus (BE) progress to oesophageal adenocarcinoma (OA). Predicting which patients progress is of vital importance for risk stratification into increased surveillance regimes or early therapeutic intervention. We have previously shown the replication licencing factors (RLF) such as polo-like kinase-1 (PLK1) may act as surrogate markers of DNA ploidy abnormalities (DNA-PA) (1) and subsequent risk of progression to OAC. This study aimed to assess whether the RLF's are up-regulated in the metaplasia-dysplasia-carcinoma sequence independently of DNA-PA. Methods: Paraffin embedded oesophageal specimens were selected from 94 patients, and pathology grade (PG) scored as 1 (squamous = Sq; n = 4), 2 (non-dysplastic BE = NDBE; n = 19), 3 (low grade dysplasia = LGD; n = 20), 4 (carcinoma in-situ = HGD/IMC; n = 36) and 5 (invasive OA = IOA; n = 15). Sections were immunostained with the antibodies PLK1-M, PLK1-L and Gem using the automated BOND-MAX system (Leica). Intensity (I) (0 to 3+) and extent (E) (0; < 1% = 1; 1–10% = 2; 10–33% = 3; 33–66% = 4; > 66% = 5) of staining were scored by 2 expert GI pathologists, and mean scores calculated. DNA-PA was assessed using image cytometry (IC). Pearson r coefficient and two-tailed P values were calculated for correlations and significance. Results: A significant correlation with extent (r = 0.87, p = 0.05; r = 0.91, p = 0.03; r = 0.99, p = 0.0008) was seen with all RLFs (PLK1-M; PLK1-L; Gem). Only PLK1-M correlated with intensity (r = 0.92, p = 0.03) and total (I+E) scores (r = 0.91, p = 0.03). Aneuploidy was present in NDBE (6%), LGD (25%), HGD/IMC (61%) and IOA (67%). The proportion of aneuploid cases/group correlated significantly with PG (r = 0.97, p = 0.007) and mean I, E and total scores for PLK1-M (r = 0.97, p = 0.008; r = 0.96, p = 0.008; r = 0.98, p = 0.96). Conclusion: All assessed RLFs were found to be significantly up-regulated in the progression to OA, with geminin scoring highest when evaluated by extent scores. Overall PLK1-M appeared the best antibody, showing additional correlation with its intensity and total staining scores with PG and DNA-PA. We further demonstrated that aneuploidy still correlates with PG as we have previously reported. In future, PLK1-M and aneuploidy may provide the basis of a biomarker panel to help guide screening and therapy for those predicted to be at increased risk of progression to OA. Disclosure of Interest: None Declared Reference: Butt MA et al. Gut 2012; 61:Suppl 2 A302